Disarming the rulers and authorities: Reading Colossians in its Roman imperial context. (November 2019) - Wright, Arthur M.
The scant scholarly discussion that focuses on the relationship between Colossians and the Roman Empire has tended to reduce the relationship to a binary proposition: either Colossians is anti-empire, or it has little to say altogether with regards to empire. Neither perspective captures the complexity of Colossians in this regard. Colossians was not written explicitly for the purpose of opposing Rome's empire. Yet it does have significant bearing on understanding how to live life faithfully under the dominion of empire. Writing to combat what the author perceives as a dangerous philosophy for the Colossian Christians, the author gives readers a glimpse into a worldview at sharp odds with Roman imperial ideology. The theological and Christological claims of the letter engage with Roman imperial ideology in ways that contest, threaten, and also mimic Roman imperial power.